Strategi Pembelajaran dalam Pendidikan Islam untuk Membentuk Karakter Siswa Sesuai Ajaran Al-Qur’an dan Hadis - Habil, Rizki Muhammad; Fauzan, Muhammad; G, Gusmaneli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The implementation of effective learning strategies in Islamic education is crucial for shaping students’ character in accordance with the values taught in the Qur’an and Hadith. Learning approaches that emphasize the internalization of faith, noble morals, and ethical attitudes through habituation, teacher role modeling, and the use of contextual learning media can foster responsible, honest, disciplined, and tolerant individuals. The application of these strategies within formal educational settings demonstrates that consistent integration of Islamic values successfully cultivates strong and virtuous character in students, preparing them to face the challenges of the modern era. Key factors supporting the success of these strategies include active teacher involvement, family support, and a conducive school environment, while major challenges arise from technological influences and social changes.